2017
DOI: 10.1186/s12885-017-3636-3
|View full text |Cite
|
Sign up to set email alerts
|

Circadian disruption promotes tumor growth by anabolic host metabolism; experimental evidence in a rat model

Abstract: BackgroundLight at night creates a conflicting signal to the biological clock and disrupts circadian physiology. In rodents, light at night increases the risk to develop mood disorders, overweight, disrupted energy metabolism, immune dysfunction and cancer. We hypothesized that constant light (LL) in rats may facilitate tumor growth via disrupted metabolism and increased inflammatory response in the host, inducing a propitious microenvironment for tumor cells.MethodsMale Wistar rats were exposed to LL or a reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…Circadian rhythms are regulated by the central oscillator SCN and the peripheral clock system, which contribute to maintaining homeostasis of physiological functions. Circadian arrhythmia is related to disorders such as neurodegenerative diseases [ 130 ], metabolic syndrome, cancer [ 131 ], and cardiovascular disease [ 132 ]. Increasing evidence demonstrates that the circadian clock systems, including the master pacemaker and peripheral circadian machinery, play pivotal roles in maintaining homeostasis of bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian rhythms are regulated by the central oscillator SCN and the peripheral clock system, which contribute to maintaining homeostasis of physiological functions. Circadian arrhythmia is related to disorders such as neurodegenerative diseases [ 130 ], metabolic syndrome, cancer [ 131 ], and cardiovascular disease [ 132 ]. Increasing evidence demonstrates that the circadian clock systems, including the master pacemaker and peripheral circadian machinery, play pivotal roles in maintaining homeostasis of bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic jet lag led to non-alcoholic fatty liver disease through metabolic disruption in the liver, which progressed to steatohepatitis and fibrosis before eventually causing hepatocellular carcinoma [143]. Rats exposed to constant light rather than normal light:dark cycles have larger tumors and they also become overweight with elevated plasma triglycerides and glucose levels [144]. The increase in tumor volume is thought to be driven by the metabolic changes induced by constant light [144].…”
Section: Circadian Control Of Metabolismmentioning
confidence: 99%
“…Rats exposed to constant light rather than normal light:dark cycles have larger tumors and they also become overweight with elevated plasma triglycerides and glucose levels [144]. The increase in tumor volume is thought to be driven by the metabolic changes induced by constant light [144].…”
Section: Circadian Control Of Metabolismmentioning
confidence: 99%
“…The associations between NAFLD, circadian rhythm disturbances, and malignancy are poorly understood. Guerrero-Vargas et al [ 43 ] recently demonstrated that constant light exposure appears to promote tumor growth in rats in a way similar to a high caloric diet. As such, the relationships between dietary content, meal timing, circadian rhythm, NAFLD, and malignancy appear complex and deserve much greater attention.…”
Section: Impact Of Time-restricted Feeding On Master and Hepatic Cmentioning
confidence: 99%